Musical appraisal in the training in Art Instructors professionals - Álverez, Elemnia; Machado Gallardo, Urbano Félix; Hernández Pérez, Elio (Didáctica y Educación ISSN 2224-2643, 2023)
The article addresses the need for students to acquire new knowledge and skills, particularly those related to Artistic Education, and their significance, while taking on ways of behaving, acting and thinking and the real possibilities of its bearer of the competencies to achieve it. The comprehension of text through the analysis of the content of the musical work constitutes an essential element that must master the future graduates to direct with quality the process of teaching learning of the Artistic Education, from the musical appreciation.